Probiotic assessment and antioxidant characterization of Lactobacillus plantarum GXL94 isolated from fermented chili - Zhou, Yingjun; Gong, Wenbing; Xu, Chao; Zhu, Zuohua; Peng, Yuande; Xie, Chunliang (Frontiers in Microbiology, 2022)
Oxidative stress is caused by an imbalance between prooxidants and antioxidants, which is the cause of various chronic human diseases. Lactic acid bacteria (LAB) have been considered as an effective antioxidant to alleviate oxidative stress in the host. To obtain bacterium resources with good antioxidant properties, in the present study, 113 LAB strains were isolated from 24 spontaneously fermented chili samples and screened by tolerance to hydrogen peroxide (H2O2). Among them, Lactobacillus plantarum GXL94 showed the best antioxidant characteristics and the in vitro antioxidant activities of this strain was evaluated extensively. The results showed that L. plantarum GXL94 can tolerate hydrogen peroxide up to 22 mM, and it could normally grow in MRS with 5 mM H2O2. Its fermentate (fermented supernatant, intact cell and cell-free extract) also had strong reducing capacities and various free radical scavenging capacities. Meanwhile, eight antioxidant-related genes were found to up-regulate with varying degrees under H2O2 challenge. Furthermore, we evaluated the probiotic properties by using in vitro assessment. It was showed that GXL94 could maintain a high survival rate at pH 2.5% or 2% bile salt or 8.0% NaCl, live through simulated gastrointestinal tract (GIT) to colonizing the GIT of host, and also show higher abilities of auto-aggregation and hydrophobicity. Additionally, the usual antibiotic susceptible profile and non-hemolytic activity indicated the safety of the strain. In conclusion, this study demonstrated that L. plantarum GXL94 could be a potential probiotic candidate for producing functional foods with antioxidant properties.